Community composition and seasonal dynamics of microplastic biota in the Eastern Mediterranean Sea - Keren Davidov; Katherine S. Marsay; Sheli Itzahri; Maxim Rubin-Blum; Paula Sobral; Chana F. Kranzler; Matan Oren (Scientific Reports)
Abstract Marine plastic pollution poses a growing environmental threat, with microplastics accumulating in the global oceans. This study profiles the seasonal dynamics and taxonomic composition of the plastisphere, the microplastic ecosystem, in the Eastern Mediterranean Sea. Using long-read 16 S and 18 S metabarcoding, we analyzed offshore microplastic and whole seawater samples across each season over a two-year period. The analysis revealed a higher richness of prokaryotic communities on microplastics compared to seawater, which was predominantly composed of Proteobacteria and Bacteroidota and exhibited notable seasonal variability. Benthic eukaryotes were enriched on microplastics compared to the surrounding seawater. Diatoms (Bacillariophyceae), in particular, showed significant enrichment within the microplastic eukaryotic community with primarily pennate diatoms of Amphora, Navicula, and Nitzschia genera, whereas the seawater included mostly centric diatoms. Seasonal fluctuations were less pronounced in the microplastic communities than in seawater, highlighting the relative stability of this new human-made ecosystem. These findings underscore the unique ecological niche of microplastic-associated communities in marine environments.